The University heritage from a GLAM persperctive. Analysis of the european university websites - Salse Rovira, Marina; Jornet, Núria; Guallar, Javier (Revista General de Información y Documentación, 2021)
Teaching and research activities have led universities to gather a very important cultural and scientific heritage. These university collections are little known to the public and many times, despite being made up of very similar materials, they appear scattered in the different information units in which university centers are organized: libraries, archives and museums, among others. The trend named GLAM (Galleries, Libraries, Archives, Museums) is aware of what unites these entities and calls for developing joint actions and presenting their heritage in a unitary way. It is studied whether the GLAM trend has penetrated the 33 best-positioned European universities in the ARWU ranking (2019). For this, their heritage websites are analyzed to see how they are organized for the treatment of their collections and if libraries and archives have a space in them. The results of the study allow us to conclude that the university heritage is still scattered, and that only since the end of the 20th century, thanks to the possibilities of the Internet, have they really started to collaborate. However, libraries and archives still have a too small role and even a low presence on the webs that show this inheritance. It would be desirable to take better advantage of the knowledge in information processing of these institutions and a system is proposed that would allow an improvement of the conditions of cultural and scientific heritage with the support of a large part of the university community and with a relevant role of libraries and files.
Keywords: university collections; university museums; university libraries; university archives; GLAM; cultural heritage; LAM; Scientific Heritage